The Effect of Problem Based Learning Model, Learning Ways and Motivation on the Entrepreneurial Attitude - Munawaroh Munawaroh; Nanik Sri Setyani (STAI Hubbulwathan Duri, 2022)
The objective of this study to reveal whether there is a significant effect of Problem based learning model, learning ways and motivation on entrepreneurial attitude. This research employed quantitative approach and ex-post facto as the research design. The number of population was 114 students. The sample was 38 students of class XI AK SMK PGRI 1 Jombang and it was selected by simple random sampling . Observations, questionnaires and documentation were applied as data collection technique and analyzed with multiple linear regression test. The results showed that the value of Ftest is 8.847 at 0,000 significant level and it is less than 0.05 which implied that there is significant effect of Problem Based Learning, learning ways and motivation on entrepreneurial attitude. The findings is there is a simultaneous and significant effect of the use of PBL model, ways of learning and motivation on entrepreneurial attitude and the regression model is Y = 66,885 + 0.865X + 0,166X + 0.003X. So in learning, the main task of teachers is to acclimatize the environment in order to support the change of learners’ behaviour.